EDUKASI PENCEGAHAN KENAKALAN REMAJA DAN PERUNDUNGAN BERBASIS HIFDZ AN-NAFS UNTUK MENINGKATKAN KESEHATAN MENTAL SISWA SMP - Abrori, Abrori; Praptawati, Destary; Haq, Baihaqi Izzul; Suudi, Ika Nur Aliffiyah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Juvenile delinquency and bullying are serious problems at the junior high school level that adversely affect students’ mental health. Therefore, preventive approaches that emphasize moral values and the protection of life are essential for creating a safe and supportive school environment. This community service program aimed to improve students’ knowledge, attitudes, and awareness in preventing juvenile delinquency and bullying through value-based training preceded by a needs assessment at SMP Negeri 1 Sumowono. The program employed a participatory educational approach using a pretest–posttest design. A total of 62 students participated, comprising 22 male and 40 female students. The intervention was delivered through counseling sessions, group discussions, and value reflection activities integrating topics on juvenile delinquency, bullying, psychological impacts, mental health, and the principles of Hifdz An-Nafs. Data were collected using knowledge and attitude questionnaires and student participation observation sheets and were analyzed using descriptive quantitative methods. The results indicated a significant improvement in students’ knowledge and attitudes following the intervention. The average level of knowledge increased by 39.1%, with the greatest improvement observed in students’ understanding of Hifdz An-Nafs values. The proportion of students with a good level of knowledge increased from 35.5% to 79.0%. In addition, positive attitudes toward bullying prevention and responsibility for maintaining mental health also showed a meaningful increase. In conclusion, value-based training on the prevention of juvenile delinquency and bullying grounded in a needs assessment is effective in enhancing students’ knowledge, attitudes, and mental health awareness and is relevant for development as a sustainable preventive strategy in school settings. ABSTRAK Kenakalan remaja dan perundungan merupakan permasalahan serius pada tingkat Sekolah Menengah Pertama yang berdampak terhadap kesehatan mental siswa. Oleh karena itu, diperlukan pendekatan pencegahan yang menekankan nilai moral dan perlindungan jiwa untuk membangun lingkungan sekolah yang aman. Kegiatan pengabdian kepada masyarakat ini bertujuan meningkatkan pengetahuan, sikap, dan kesadaran siswa dalam mencegah kenakalan remaja dan perundungan melalui pelatihan berbasis nilai yang didahului oleh Need assessment di SMP Negeri 1 Sumowono. Kegiatan dilaksanakan menggunakan pendekatan edukatif partisipatoris dengan desain pretest–posttest. Peserta berjumlah 62 siswa, terdiri atas 22 siswa laki-laki dan 40 siswa perempuan. Intervensi diberikan melalui penyuluhan, diskusi kelompok, dan refleksi nilai yang mengintegrasikan materi kenakalan remaja, perundungan, dampak psikologis, kesehatan mental, serta prinsip Hifdz An-Nafs. Data dikumpulkan menggunakan kuesioner pengetahuan dan sikap serta lembar observasi partisipasi siswa, kemudian dianalisis secara deskriptif kuantitatif. Hasil menunjukkan adanya peningkatan signifikan pada pengetahuan dan sikap siswa setelah pelatihan. Rata-rata pengetahuan meningkat sebesar 39,1%, dengan peningkatan tertinggi pada pemahaman nilai Hifdz An-Nafs. Proporsi siswa dengan tingkat pengetahuan baik meningkat dari 35,5% menjadi 79,0%. Selain itu, sikap positif terhadap pencegahan perundungan dan tanggung jawab menjaga kesehatan mental juga mengalami peningkatan yang bermakna.Pelatihan pencegahan kenakalan remaja dan perundungan berbasis Need assessment efektif meningkatkan pengetahuan, sikap, dan kesadaran kesehatan mental siswa, serta relevan untuk dikembangkan sebagai strategi preventif berkelanjutan di lingkungan sekolah.